Travelling to the described present: mago-space in the Strugatskys’ Monday starts on Saturday - Tuliakova, Natalia; Nikitina, Natalia (Studia Rossica Posnaniensia, 2021)
Fantasy and science fiction genres extensively use imaginary settings and locations different from realistic ones but striving to look real. Arkady and Boris Strugatsky, pioneers of the science fiction genre in Russia, actively exploited the potential of both genres in their early tale, Monday starts on Saturday (1964), which combines features of the two space types. The present paper analyses the principles of creating ‘mago-space’ in the book. To do so, we look at the spatial organization of the events involved in the plot and the personages’ ideas regarding space. The research will enable us to clarify the role of space in conveying the authors’ message, which in this tale is quite explicit. We argue that the space changes significantly within the book, accompanying genre transformations and the development of the protagonist. Since the tale uses ‘mental sublocations’ as the main units of spatial organization, each part is determined by a certain type of cultural heritage. In the first part, it is the mental space of folklore and classical literature, in the second – that of mythology and science fiction, and in the final – philosophy and science. Mental spaces that coexist and follow various laws form a narrative which turns out to be a journey to the described present in the variety of its forms.